Penerapan Kaidah Ushul Fiqih dalam Menafsirkan Teks Al-Qur’an - Yuli Edi Z, M. Khai Hanif; Rahman , Pathur; Jemain , Zulkipli (Jurnal Kajian Pendidikan Islam, 2024)
This article discusses the application of fundamental principles of Islamic jurisprudence (Usul al-Fiqh) in the interpretation of the text of the Quran. Several principles are discussed in this article, including 'Al- Ibroh bi Umumi Lafdz Laa bi Khususis Sabab' (generalization by wording rather than specificity of the cause), the principle of 'Amr and Nahyi' (command and prohibition), 'Mafhum Muwafaqoh and Mukholafah' (conformity and contradiction in meaning), 'Al-Aslu fi Ashya' Ibahah' (the presumption of permissibility in matters where the law is unclear), and 'Jalbu al-Maṣâliḣ wa Dar`u al-Mafâsid' (promotion of benefits and prevention of harm). This article extensively discusses each of these principles of Usul al-Fiqh and highlights the importance of their application within the context of Quranic interpretation. The research underscores that the application of these principles aids in interpreting the Quranic text more accurately, avoiding common interpretational errors, and understanding the Islamic laws contained within the sacred text. In conclusion, the application of Usul al-Fiqh principles is crucial for ensuring a correct and relevant understanding of the Quran. This approach not only assists in avoiding misinterpretations but also aids in comprehending the Islamic jurisprudence encapsulated within this holy scripture.